A celebração de negócios jurídicos nas ações de improbidade administrativa por parte do Ministério Público - Medeiros, Sara Julianne Bezerra de (Universidade Federal Rural do Semi-Árido, 2019)
This article aims to demonstrate as lege ferenda the possibility of making transactions in actions of administrative improbity, with the modification in art. 17, §1º of Law no. 8,429/92. Bibliographic research and the deductive method were used in the development of the three stages of this article. At first, for a broad understanding, it were presented the general aspects about the administrative improbity and the implications of the prohibition of using plea bargain, making agreements or using means of conciliation. The aim of this article is to clarify that legal transactions are effective tools for the compensation of damages caused to public assets, since the sluggishness of the judiciary, among other factors, impairs the claim of efficient repair by traditional way. The changes brought in the Brazilian procedural scenario by the Laws no. 12,850/2013 (award-winning collaboration), no. 12.846/2013 (leniency agreement), no. 11.340/2015 (mediation law), and n. 13.105/2015 (Code of Civil Procedure), which established the use of alternative dispute resolution methods, were demonstrated. Moreover, the Public Prosecution's performance in the execution of legal transactions, as custos legis, was demonstrated. Lastly, it were presented considerations about the necessity and relevance of legal transactions in the fight against corruption in Public Administration and about the incompatibility that the prohibition brought by art. 17, §1º of Law no. 8.429/92 represents within the new Brazilian socio-legal context
Artigo Acadêmico
Keywords: Improbidade administrativa; Negócios jurídicos; Métodos Alternativos; Administrative improbity; Legal transactions; Alternative Methods; CIENCIAS SOCIAIS APLICADAS::DIREITO